IMMUNOPHYSIOLOGICAL INDICES OF CALVES UNDER THE INFLUENCE OF ANTIMICROBIAL MEDICINAL PRODUCT CEFINEL - Лісова, Н. Е.; П’ятничко, О. М.; Максимович, О. А.; Бассараб, В. П.; Михалусь, Г. М. (Scientific Progress & Innovations, 2013)
The article analyzed the dynamics of immunological and biochemical indices of calf organism at application of antimicrobial medicinal product Cefinel. The results of conducted tests showed the influence of medicinal product on cell factors of organism resistance. Received data of leucogram and protein metabolism had positive prognostic significance and showed therapeutic efficacy of Cefinel. Research has established that after the course of antibiotics to animals in the experimental calves’ hemogram was normalized.